(untitled) (International Journal of Advanced Technology and Social Sciences (IJATSS), 2024)
The aim of this research is to analyze the pattern and application of final assignment guidance student of the RPL program, PG PAUD FIPP UNY study program. This research uses a descriptive qualitative approach. Starting with conducting secondary data analysis regarding descriptions related to the material and activities that have been carried out in the online thesis final assignment guidance pattern. Data collection techniques were carried out using observation, interviews, and documentation. The research subjects as data sources in this research were students and the technical team of RPL program students from the PG PAUD FIPP UNY study program. The materials and guidance modes applied included WhatsApp, Google Meet, Zoom, SMS, and Telephone with their respective advantages and disadvantages